DIVERSIFICATION OF OIL AND GAS COMPANIES’ ACTIVITIES IN THE CONDITION OF OIL PRICES REDUCTION AND ECONOMIC SANCTIONS - A. V. Sheveleva; L. B. Akieva (Vestnik MGIMO-Universiteta)
This article analyzes the influence of the economic sanctions imposed from the USA and the EU and oil prices reduction on the oil and gas companies and the directions of diversification of their activity as a method of management of price risks are considered. In the modern dynamic and quickly developing world, in the conditions of globalization and market economy, the oil and gas companies are affected by various risks which can exert negative impact on production and financial results. Risks can arise in absolutely various spheres, beginning from natural and technological hazards, and finishing with price risks. Sharp reduction of oil prices and decrease in demand for energy resources in the world markets, first of all in the European countries, input of financial or technological sanctions from the USA and Europe against Russia in 2014 has caused necessity of search a new more effective methods of price risks management of the oil and gas company. The methods of price risk management include the creation of commodity reserves, the establishment of a reserve fund, long-term contracts, subsidies from the state and the diversification of activities. The most effective it is possible to offer diversification of oil and gas companies' activity. It is expedient to carry out diversification of oil and gas companies' activity in such directions as geographical diversification of the oil, oil products and gas realization directions, geographical diversification of oil and gas companies' purchasing activity, diversification of oil, oil products and gas transportation ways, diversification of oil and gas companies' business. This approach allows to expand the activities of the oil and gas companies and create additional ways to generate revenue and enhance efficiency of oil and gas companies.